2015
DOI: 10.1371/journal.pone.0126866
|View full text |Cite|
|
Sign up to set email alerts
|

Deletion of Protein Tyrosine Phosphatase 1B (PTP1B) Enhances Endothelial Cyclooxygenase 2 Expression and Protects Mice from Type 1 Diabetes-Induced Endothelial Dysfunction

Abstract: Protein tyrosine phosphatase 1B (PTP1B) dephosphorylates receptors tyrosine kinase and acts as a molecular brake on insulin signaling pathway. Conditions of metabolic dysfunction increase PTP1B, when deletion of PTP1B protects against metabolic disorders by increasing insulin signaling. Although vascular insulin signaling contributes to the control of glucose disposal, little is known regarding the direct role of PTP1B in the control of endothelial function. We hypothesized that metabolic dysfunctions increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Similarly female Ay mice exhibit a reduced acetylcholine-mediated dilation (Figure 2B) with no alteration of sodium nitroprusside–mediated relaxation (Figure 2D). Consistent with the literature, 11,33 Ptp1b deletion did not impair endothelial function in male mice, despite hypertension. Similarly, obesity and hypertension did not reduce acetylcholine-mediated relaxation in male Ay mice (Figure S3).…”
Section: Resultssupporting
confidence: 91%
“…Similarly female Ay mice exhibit a reduced acetylcholine-mediated dilation (Figure 2B) with no alteration of sodium nitroprusside–mediated relaxation (Figure 2D). Consistent with the literature, 11,33 Ptp1b deletion did not impair endothelial function in male mice, despite hypertension. Similarly, obesity and hypertension did not reduce acetylcholine-mediated relaxation in male Ay mice (Figure S3).…”
Section: Resultssupporting
confidence: 91%
“…A main finding of this study is that PTP1B is a negative regulator of VEGF-induced angiogenesis in endothelial cells, consistent with the recently unraveled contribution of PTP1B in endothelial cell signaling (8,10,26). In a mouse hindlimb ischemic angiogenesis model, PTP1B expression and activity were increased (8).…”
Section: Calpain/ptp1b Axis In Vegfr2 Regulation and Angiogenesissupporting
confidence: 88%
“…8). It is reported that PTP1B expression is increased in mouse aortic endothelial cells of diabetic animals (26). These results indicate that PTP1B may act to negatively counteract endothelial angiogenesis in diabetic environment.…”
Section: Calpain/ptp1b Axis In Vegfr2 Regulation and Angiogenesismentioning
confidence: 65%
“…To the best of our knowledge, this is the first direct demonstration that prevention of endothelial dysfunction per se leads to a reduction of CHF. We 3,16 and others [20][21][22] previously revealed that PTP1B is a target for the prevention of endothelial dysfunction, in the context of diabetes mellitus, obesity, and CHF. Many mechanisms may indirectly contribute to this protective effect, especially in the context of chronic in vivo inhibition or gene deletion.…”
Section: Discussionmentioning
confidence: 95%